Maternal Life Satisfaction and Child Development from Toddlerhood to Adolescence - Nabanita Datta Gupta; Jonas Jessen; C. Katharina Spiess (Institute of Labor Economics (IZA), 2023)
In this paper we analyse the association between maternal well-being and child develop- ment at different ages. We use data from the German Socio-Economic Panel (SOEP) which captures maternal life satisfaction and numerous cognitive and non-cognitive child development outcomes. We identify a strong positive association between mothers' life satisfaction and their children's development when these are toddlers (2-3 years, VAB scores), of primary school age (5-10 years, SEB scores and Big 5) and in adolescence (11-14 years, life satisfaction, school grades and self-reported Big 5). This relationship holds when we control for a wide range of potentially confounding factors, including maternal education, employment, household income and maternal personality traits. We confirm our main findings with an IV estimation where we instrument contemporaneous maternal life satisfaction with that measured pre-birth and with a value-added model as some child outcomes are observed twice at different ages. Our findings suggest that mothers' life satisfaction is beneficial for their children's development at all ages and that it is fruitful for policy makers to identify measures through which maternal well-being can be raised.
Keywords: J13; I22; 330; life satisfaction; subjective well-being; mothers; child development; skill formation